Characterization of Curcumin as a Coating Material for Polymer-Free Stents in Terms of Morphology and Release - Putri Akhmad Yani, Ameliyana Rizky Syamara; Herliansyah, Muhammad Kusumawan (Universitas Negeri Malang, 2025)
The use of bare metal stents over the long term often leads to the re-narrowing of blood vessels, prompting a shift to drug-eluting stents (DES). However, the use of polymers in DES has been known to trigger inflammation and thrombosis in the arteries. As an alternative, polymer-free drug-eluting stents (PF-DES) have emerged as a safer option. In this study, curcumin was selected as the primary coating material for PF-DES using the electrophoretic deposition method. The effects of varying curcumin concentrations (125 µg/ml, 250 µg/ml, and 500 µg/ml) were examined to understand their impact on deposition morphology, coating weight, chemical bonding characteristics, and curcumin release using scanning electron microscopy, ultraviolet-visible spectrophotometry, and Fourier transform infrared spectroscopy. The results showed that increasing the amount of curcumin resulted in a heavier and rougher coating, with deposition weights of 573.22 μg/cm², 1198 μg/cm², and 11954 μg/cm², after coated with curcumin concentrations of 125 µg/ml, 250 µg/ml, and 500 µg/ml, respectively. The curcumin release process was comprised of three phases: an initial burst, a slower release, and a second burst, which completed the release over more than 40 days. The efficacy of curcumin as a coating for PF-DES facilitates a controlled and steady release of the drug.